How are Youth Employment Programs Adapting to COVID-19? - Singh, Sunamika; Joseph, Kavell (World Bank, Washington, DC, 2020)
This brief is part of the solutions for youth employment (S4YE) knowledge brief series focusing on the design and implementation of youth employment programs. In this knowledge brief, the authors highlight different ways in which youth employment projects in S4YE’s community of practice, the impact portfolio, are adapting their strategies and delivery models in response to Coronavirus 2019 (COVID-19). Based on recent and ongoing discussions with the partners, the authors see six main trends that programs are using to maintain operational and programmatic continuity. These include scaling of virtual operations, crowdsourcing ideas from youth, accelerating remote learning, encouraging youth voice, increased support for micro, small and medium enterprises, and leveraging new growth opportunities. Overall, the authors see a deepening and widening of the ways the partners are using digital technology to be effective and to reach more youth in these challenging times.